Association of household food insecurity with sociodemographic factors and obesity in US youth: findings from the National Health and Nutrition Examination Survey 2017–2018 - Mokari-Yamchi, Amin; Faghfouri, Amir Hossein; Gholami, Samira; Nattagh-Eshtivani, Elyas; Gheibi, Shahsanam (Frontiers in Public Health, 2024)
The objective is to determine the prevalence of household food insecurity (HFI) based on sociodemographic factors and their relationship to obesity in youth.The study included a sample of 1,962 youth (aged 6-18) from the National Health and Nutrition Examination Survey (NHANES). The US Household Food Security Survey Module is used to measure food security over the past 12 months. Logistic regression models were used to estimate adjusted odds ratios (ORs) while controlling for covariates.In total, 27.4% of the individuals surveyed experienced HFI. Youth from food insecure households were more likely to be obese (adjusted odds ratio [aOR]: 1.59 [95% confidence interval: 1.19-2.13]) and also having abdominal obesity (aOR: 1.56 [95% CI: 1.19-2.03. however, factors such as non-Hispanic ethnicity, having a Head of household with a college degree, and households with an income exceeding 350% of the poverty line were associated with a reduced risk of facing HFI.Hispanic individuals, households with lower parental education levels, and lower family incomes, are disproportionately affected by food insecurity. Furthermore, HFI has been associated with an increased risk of overweight and abdominal obesity among youth.Addressing FI requires targeted policies and interventions that prioritize vulnerable groups.